Oleylphosphocholine (OlPC) arrests Cryptosporidium parvum growth in vitro and prevents lethal infection in interferon gamma receptor knock-out mice - Sonzogni-Desautels, Karine; Renteria Flores, Axel; Vasquez Camargo, Fabio; Di Lenardo, Thomas Z.; Mikhail, Alexandre; Arrowood, Michael J.; Fortin, Anny; Ndao, Momar (Frontiers in Microbiology, 2015)
Cryptosporidium parvum is a species of protozoa that causes cryptosporidiosis, an intestinal disease affecting many mammals including humans. Typically, in healthy individuals, cryptosporidiosis is a self-limiting disease. However, C. parvum can cause a severe and persistent infection that can be life-threatening for immunocompromised individuals, such as AIDS patients. As there are no available treatments for these patients that can cure the disease, there is an urgent need to identify treatment options. We tested the anti-parasitic activity of the alkylphosphocholine oleylphosphocholine (OlPC), an analog of miltefosine, against C. parvum in in vitro and in vivo studies. In vitro experiments using C. parvum infected human ileocecal adenocarcinoma cells (HCT-8 cells) showed that OlPC has an EC50 of 18.84 nM. Moreover, no cell toxicity has been seen at concentrations ≤50 µM. C57BL/6 interferon gamma receptor knock-out mice, were infected by gavage with 4000 C. parvum oocysts on Day 0. Oral treatments, with OlPC, miltefosine, paromomycin or PBS, began on Day 3 post-infection for 10 days. Treatment with OlPC, at 40 mg/kg/day resulted in 100% survival, complete clearance of parasite in stools and a 99.9% parasite burden reduction in the intestines at Day 30. Doses of 30 mg/kg/day and 20 mg/kg/day also demonstrated an increased survival rate and a dose-dependent parasite burden reduction. Mice treated with 10 mg/kg/day of miltefosine resulted in 50% survival at Day 30. In contrast, control mice, treated with PBS or 100 mg/kg/day of paromomycin, died or had to be euthanized between Days 6 and 13 due to severe illness. Results of parasite burden were obtained by qPCR and cross-validated by both flow cytometry of stool oocysts and histological sections of the ileum. Together, our results strongly support that OlPC represents a potential candidate for the treatment of C. parvum infections in immunocompromised patients.